Towards a net zero built environment: decarbonisation of the UK cement industry - Ning Li; Cise Unluer (npj Materials Sustainability)
Abstract Cement production contributes ~7–8% of global anthropogenic CO2 emissions, necessitating urgent decarbonisation. In the UK, focus has shifted to modernising infrastructure with low-carbon solutions. This review examines strategies involving alternative binders, supplementary cementitious materials, and carbon capture, utilisation, and storage technologies. Promising advancements include low-carbon cements and industrial by-product integration. Practical guidelines address regulatory barriers, technology scaling, and economic viability, emphasising the UK’s role in advancing cement industry’s decarbonisation.